Ageing and Health - Greer, Scott L.; Lynch, Julia; Reeves, Aaron; Falkenbach, Michelle; Gingrich, Jane; Cylus, Jonathan; Bambra, Clare (Cambridge University Press, 2022)
Ageing societies can be healthy and productive- if they get the politics right. This book argues that the population ageing crisis can be solved through policies that reduce inequalities between and within generations. It then explores the political coalitions needed to support policymaking that avoids pitting generations against each other.